Unrevealing the Role of Social Media on Online Sex Trafficking: A Case Study and Conceptual Model of Cyber Prostitution in Indonesia - Usman, Sahda Armandiva; Budiman, Kholiq (Department of Computer Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2023)
Online prostitution is an example of cybercrime which is increasingly happening in today's digital era. Even though online prostitution cases have been well documented, in Indonesia itself there is no criminal law regulation that specifically addresses prostitution cases that occur on social media. Likewise, there is a lack of research that discusses the process of how online prostitution cases can occur from start to finish and social media interventions in these cases. The average previous research only focused on law violations that occurred at the final stage or at the exploitation stage. This indirectly ignores the role of social media in the process of building trust between perpetrators and victims (trust building), the process of trading or advertising (advertising), and the process of transactions between perpetrators and potential buyers (transactions). Therefore, in this study the author will discuss the role of technology in online prostitution cases and their relationship with criminals, victims and members of the police. The research design used by the author is Research & Development Level 1. The data in this study were obtained using in-depth interviews with informants and analysed by a deductive approach adapted from Nunamaker's research. Based on the results of the data analysis that has been carried out, the author finds that the social media most used by the actors is the MiChat application as much as 44%, Facebook 26%, WhatsApp 12% and other applications as much as 18%. In addition, this research also produces a conceptual model that describes the various processes that occur in online prostitution cases and the role of each social unit and social media. The conceptual model has been tested and validated by experts using the rating scale method. Obtained a percentage value of 86.67%. The results of this assessment prove that the conceptual model created is very feasible.